Retrograde Tibiopedal Access as a Bail-Out Procedure for Endovascular Intervention Complications - Ahmed Amro; Alaa Gabi; Adee Elhamdani; Naveed Iqbal; Mehiar El-Hamdani (Case Reports in Vascular Medicine)
Introduction. Retrograde pedal access has been well described in the literature as a secondary approach for limb salvage in critical limb ischemia (CLI) patients. In this manuscript we are presenting a case where retrograde tibiopedal access has been used as a bail-out procedure for the management of superficial femoral artery (SFA) intervention complications. Procedure/Technique. After development of a perforation while trying to cross the totally occluded mid SFA using the conventional CFA access, we were able to cross the mid SFA lesion after accessing the posterior tibial artery in a retrograde fashion and delivered a self-expanding stent which created a flap that sealed the perforation without the need for covered stent. Conclusion. Retrograde tibiopedal access is a safe and effective approach for delivery of stents from the distal approach and so can be used as a bail-out technique for SFA perforation.